1978
DOI: 10.1210/jcem-47-1-18
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Parathyroid Hormone on Plasma Prolactin in Man

Abstract: The iv infusion of parathyroid extract or the synthetic fragments of 1-34 bovine or human parathyroid hormone produced a rapid and marked increase of plasma PRL in normal subjects. The stimulation of the release of endogenous parathyroid hormone by administration of disodium EDTA also resulted in a parallel increase of plasma PRL. Parathyroid hormone did not act via plasma cAMP, as the plasma level reached by this nucleotide was too small to produce PRL release. The ingestion of L-dopa 2 h before parathyroid h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
1
1

Year Published

1984
1984
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(27 citation statements)
references
References 18 publications
0
25
1
1
Order By: Relevance
“…On the other hand, Kokot et al [12] found an increased disappearance rate of plasma prolactin in patients with acute renal fail ure suggesting that the hyperprolactinemia is due to increased production and/or release of prolactin. Isaac et al [7] found that the administration of PTH or the acute rise in serum levels of endogenous PTH is associated with a significant rise in scrum levels of prolactin in normal subjects. It is possible that the state of secondary hyper parathyroidism in patients with acute renal failure is at least partly responsible for the elevated serum levels of prolactin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Kokot et al [12] found an increased disappearance rate of plasma prolactin in patients with acute renal fail ure suggesting that the hyperprolactinemia is due to increased production and/or release of prolactin. Isaac et al [7] found that the administration of PTH or the acute rise in serum levels of endogenous PTH is associated with a significant rise in scrum levels of prolactin in normal subjects. It is possible that the state of secondary hyper parathyroidism in patients with acute renal failure is at least partly responsible for the elevated serum levels of prolactin.…”
Section: Discussionmentioning
confidence: 99%
“…The serum levels of testosterone in these patients are usually low and those of luteinizing hormone (LH) and prolactin are ele vated [2-6], The mechanisms responsible for these hor monal derangements are not well understood. Parathy roid hormone may stimulate prolactin release [7] and the state of secondary hyperparathyroidism of uremia [8][9][10] may be, at least partly, responsible for the hyperprolacti nemia. The elevated levels of prolactin may in turn affect testosterone secretion [11] and contribute to the low serum levels of the latter.…”
mentioning
confidence: 99%
“…The demonstration of resistance to stimulation or suppression of prolactin in CRF is consistent with increased autonomous production (Pece 1979). The state of secondary hyperparathyroidism of CRF may contribute to the increased production rate of prolactin, because PTH stimulates prolactin secretion (Issac 1978). The treatment of CRF patients with erythropoietin was associated with a decreased in serum prolactin levels and improvement in sexual dysfunction (Schaefer, Stanhope et al 1989), but did not normalize rate of the response to TRH (Ramirez 1976).…”
Section: Hyperprolactinemiamentioning
confidence: 99%
“…On the other hand, dopamine infusion or the administration of L-dopa fails to decrease basal prolactin levels. In chronic renal failure, increased prolactin secretion may be related in part to the development of secondary hyperparathyroidism (42,43). Bromocryptine can reduce plasma prolactin levels in patients with chronic renal failure, but there has been an inconsistent effect on sexual potency and libido (41).…”
Section: Disorders Associated With Testicular Failurementioning
confidence: 99%